Daily activity budget of Proboscis monkey (Nasalis larvatus) in captivity: with a focus on agonistic behaviour / Nur Izatie Ismail - Ismail, Nur Izatie (2014)
The behaviour of the proboscis monkey was studied for a period of three weeks with total of 106.875 hours of observations. The study was conducted to determine the behaviour of the proboscis monkey in captivity and to observe the agonistic behaviour of the monkeys in zoo. The data collection was conducted using non-focal sampling and all-occurrence sampling (Altmann, 1974). Two major behaviours of the proboscis monkeys are feeding (OMU: 28.8%, AMU: 26.5%) and resting (OMU:32%, AMU: 33%). The recorded agonistic behaviours made up 5 to 10% of total activity budget and higher than the wild population, which is less than 1%. Visitor presence was found significantly affect the behaviour of the proboscis monkey in captive.